THE INFLUENCE OF PERCEPTION INTERVENING ON HOUSEHOLD PHARMACEUTICAL WASTE DISPOSAL METHODS IN SURABAYA - Milhan, Rumaisha
Household pharmaceutical waste disposal in the form of unused and expired medicines has the potential to increase contamination to the environment due to long-term exposure. Contamination of pharmaceutical waste causes toxicity to the environment, death of fauna and antibiotic resistance. This study aims to determine the perception and disposal method, the mediating effect of perception on the disposal method, as well as a descriptive study of related policies. The research was conducted in the city of Surabaya as the second big city in Indonesia using questionnaires and interviews (mixed methods). Perceptions were investigated quantitatively and qualitatively using the RANAS model (Risk, Attitude, Norm, Ability, Self-regulation factors). Analysis of the influence and type of perception mediation as an intervening variable on the disposal method using pathway analysis with six regression models. The independent variable has a simultaneous effect on each RANAS factor and general perception. Only age affects the disposal method directly. Exposure to information and knowledge affect the method either partially, simultaneously, or mediated by intervening variables. Those six regression models can be used to predict disposal method with each RANAS factor and general perception as intervening variables. All intervening variables were able to produce perfect mediation. The policy on guidelines for disposing of drugs at home from BPOM is in accordance with US EPA, US FDA, and WHO guidelines. However, the implementation of the "Ayo Buang Sampah Obat" program has not been maximized due to the limitations of the drug waste dropbox infrastructure at the Surabaya City pharmacies. Interventions according to RANAS are carried out by increasing the provision and distribution of dropboxes as well as direct socialization by policy makers and social media.